Dental and prosthodontic status of an over 40 year-old population in Shandong Province, China - Creugers Nico HJ; Bronkhorst Ewald M; Witter Dick J; Zhang Qian (BMC, 2011)
Abstract Background This study aims to (1) describe the dental status using DMFT for the whole dentition and the anterior, premolar and molar regions; (2) determine associations of demographic variables and socio-economic status (SES) with DMFT and tooth replacement; (3) analyze to what extent the goal as proposed by the WHO -'the retention of not less than 20 teeth throughout life' is achieved. Methods DMFT and tooth replacement data of 1588 subjects over 40 years from urban and rural sites in Qingdao (Shandong Province, China) were collected. Relative D, M, and F scores per dental region were calculated and compared by paired T-tests. Multivariable logistic regression was used to determine relationships with age, gender, place of residence, and SES. Results Mean numbers of D and F were low (1.36 respectively 0.27) at all ages. Molars had highest chance for D and M. For the molar region every additional year of age gave significantly lower chance for D and higher chance for M (OR: 0.98 and 1.02 respectively; both p ≤ 0.01). Mean number of M was associated with age (approximately 1.5 in each jaw at 40 years and 6 at 80 years). Females had higher chance for D (OR: 1.34; p ≤ 0.05) and F (OR: 1.69; p ≤ 0.01), and lower chance for M (OR: 0.60; p ≤ 0.01). Urban and rural subjects had similar chance for D; urban subjects had approximately 5 times more chance for F (p ≤ 0.01). SES had no relationship with D and M, however SES low was associated with F (OR: 0.45; p ≤ 0.01). Replacements were significantly associated with age (all dental regions except anterior region), gender (all dental regions), place of residence (whole dentition and molar region), and SES (whole dentition and premolar and molar regions). Conclusions The majority of subjects presented a reduced dentition. Molars were most frequently affected by D and M. D, M, F and replaced teeth were associated with the background variables, however differently for different dental regions. Above the age of 70 years, only 64% of the subjects presented 'not less than 20 natural teeth'.